Assessing ‘patient safety culture’ in maternity obstetric units in the Umgungundlovu District, Kwazulu-Natal - Thakur-Rajbansi, Shameen (My University, 2020)
This study set out to understand the perceptions of maternal healthcare providers (MHCPs) towards patient safety culture (PSC), in selected public hospital maternity obstetric units (MOUs) in the UMgungundlovu District in KwaZulu-Natal. The aim was to guide safety improvement initiatives and strengthen the clinical governance framework, by assessing the level of PSC. The assumption was that MOUs should be functioning theoretically like High Reliability Organisations (HROs) to prevent maternal deaths. However, this district had a high Maternal Mortality Ratio (MMR) of 208.3 maternal deaths per 100 000 live births in 2015, whilst the Millennium Development Goal5 was 38/100 000 live births. Donabedian’s (1980) Model of Care conceptual framework was used made up of structure, process and outcomes, with the focus mainly on ‘process,’ outcomes and MHCP interpersonal skills. The methodology involved distributing an expanded version of the validated15 item short format PSCHO survey to MHCPs. The survey consisted of six topics key to a culture of patient safety, including demographic data. Data was collected over a 6 week period, from April to May 2018.A total of 245 MHCPs, comprising of all gynaecologists’, obstetricians’, doctors’, clinical and nursing managers’, together with a sample of midwives’ and advanced midwives’, were systematically selected. The total number of respondents was 197, however 5 surveys had missing data, hence (n=192). The overall response rate was 78.1%. Results were interpreted by the frequency of problematic and neutral responses obtained, which either implied a lack (absence) or low level of safety culture. Responses per question were collated according to job designation, work experience and age. Overall, the Mean of problematic responses was 31.01% and 14.5% for neutral responses. The perceptions of MHCPs with respect to PSC varied slightly amongst doctors’, midwives’ and managers’. It can be concluded that PSC does not mimic HROs sufficiently in the uMgungundlovu District MOUs, with 63.5% (n = 122) MHCPs giving a poor to adequate score. However, a key Correlation finding was that both PSC and MMR are inextricably linked, i.e. as PSC improves, MMR outcomes also improves. Future research is required to verify the results and find ways that senior managers’ can commit to patient safety change management
A research report submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation), 2020